Integration of Community-Based on Tour Packages to Realize A Sustainable Tourism Village: The Case of Penadaran Tourism Village Grobogan Regency Central Java - Palupi, Santi; Bahri, Asep Syaiful; Aditantri, Rahmatyas; Baskoro, Aloysius; Priyanto, Sony Heru (E-Journal of Tourism; Volume 11 Number 1 (March 2024), 2024)
Penadaran Village, Gubug District, Grobogan Regency, Central Java, is a village that has very diverse tourism potential, both natural, cultural and artificial potentials. Currently, the village has been included in the top 300 of the Indonesian Tourism Village Award in 2023. Initial studies show that Penadaran Village does not yet have a strategy on how to develop a tourism village, even though the village has the potential to be used as tourism activities such as tour packages, homestays and traditional culinary. This is because there are still many elements of society who do not understand about tourism villages and the management of tourism village products. Based on this, the purpose of this study is to integrate the tourism potential of Penadaran Village into a tour package that involves the community. The primary data collection technique used in the study was using focus group discussion (FGD) which was attended by the community, tourism awareness groups, village government officials and local entrepreneurs. The data analysis technique used is descriptive analysis that describes the results of FGD. The results achieved in this study are the compilation of several tour packages consisting of one-day tour packages, two-day one-night tour packages and three-day and two-night tour packages.